The Impact of COVID-19 on Economic Growth of Countries: What Role Has Income Inequality in It? - Mahieddine Adnan Ghecham (Economies, 2022)
This paper argues that income inequality explains the variation in the economic performance of different countries over the first year of the COVID-19 pandemic. Unlike the conclusions reported by some studies, this study shows that health casualties caused by COVID-19 has had a higher adverse economic impact on countries with lower income inequality. Notwithstanding, the decline in the economic growth as well as the number of casualties caused by COVID-19 are, overall, proportionate to the level of income inequality of the country. Furthermore, the results show that countries with more dependence on the service sector and countries that implemented more restrictive measures (lockdowns) experienced a higher decline in GDP growth over the first year of the pandemic period. The paper concludes with some important policy implications that support the role of strong institutions in making economies resilient over a period of pandemic.